Personalized Diagnosis and Therapy for Multiple Sclerosis - Ramo-Tello, Cristina M. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
We all agree that people with MS need to be cared in a profoundly personalized way. The care of the patient with MS is still based on the presence of relapses, so their successful diagnosis and treatment is fundamental and will condition the therapeutic strategies to follow with the patient. The treatment strategies are a highly controversial topic of debate that is increasingly supported by robust objective biological markers of response and that also increasingly take into account the dynamics and predictors of cognitive impairment along the disease course, which includes the adoption of new trends in the field of machine learning techniques. However, we all know that patient care goes beyond being treated with drugs and we cannot overlook reminding patients of the importance of their lifestyle behaviors that vary according to the MS phenotype, in order to improve their quality of life. Teleconsultation is a new care strategy proved to be feasible and well-received by patients with MS that will undoubtedly become reinforced because it will allow a closer follow-up of the patient without the need for displacement.